A geometric morphometric approach to the study of sexual dimorphism in the modern human frontal bone. Issue 4 (6th October 2020) - Del Bove, Antonietta; Profico, Antonio; Riga, Alessandro; Bucchi, Ana; Lorenzo, Carlos
Abstract: Objectives: We analyzed the main anatomical traits found in the human frontal bone by using a geometric morphometric approach. The objectives of this study are to explore how the frontal bone morphology varies between the sexes and to detect which part of the frontal bone are sexually dimorphic. Materials and methods: The sample is composed of 161 skulls of European and North American individuals of known sex. For each cranium, we collected 3D landmarks and semilandmarks on the frontal bone, to examine the entire morphology and separate modules (frontal squama, supraorbital ridges, glabellar region, temporal lines, and mid‐sagittal profile). We used Procrustes ANOVAs and LDAs (linear discriminant analyses) to evaluate the relation between frontal bone morphology and sexual dimorphism and to calculate precision and accuracy in the classification of sex. Results: All the frontal bone traits are influenced by sexual dimorphism, though each in a different manner. Variation in shape and size differs between the sexes, and this study confirmed that the supraorbital ridges and glabella are the most important regions for sex determination, although there is no covariation between them. The variable size does not contribute significantly to the discrimination between sexes. Thanks to a geometric morphometric analysis, it was found that the size variable is not an important element for the determination of sex in the frontal bone. Conclusion: The usage of geometric morphometrics in analyzing the frontal bone has led to new knowledge on the morphological variations due to sexual dimorphism. The proposed protocol permits to quantify morphological covariation between modules, to calculate the shape variations related to sexual dimorphism including or omitting the variable size. Abstract : Shape variation associated to the female (left) and male (right) morphology.